SCREENLESS DISPLAY TECHNOLOGY (International Journal of Engineering and Computer Science, 2018)
Technological advancement nowadays is moving to a faster pace. The latest display technology -Touch Screen Display, commonly used in our smart phones and tablet computers will move to a mere history in the coming future. Lack of space is one of major problem faced by screen displays. This emerging new display technology will replace this touch screen environment and will solve the problems at higher level, making life more comfortable. The main aim of the Screenless Display is to display or transmit the information without the help of a screen or the projector. Using this display, we can directly project images onto the human retina, open space and even to the human brain. It avoids the need of high weight hardware and it will provide privacy at a high rate. This field came into progress during the year 2013 by the arrival of products like holographic videos, virtual reality headsets, retinal displays, mobiles for elderly, eye tap etc. At present, we can say that only part of the Screenless Display Technology is brought up which means that more advancement is necessary for a boost in the technology. This problem will surely provide a pathway for screenless display.